Matar-se em nome de Deus?: uma análise do suicídio praticado pelos homens e mulheres bombas no islamismo - Camargo, Valéria Lúcia de (2007)
This work aims to research the suicides that are committed by muslin human bombers, a particular phenomenon usually referred to religious purposes and whose destruction is terrifying the world for its cruel and spectacular forms of destruction. The main purpose of this research is to report and to analyze some works of non muslin writers in order to point out the actual situation of suicide attackers and their positions about it. Afterwards, several questions are arisen to further studies for scientists of religion. This theme was pointed as being very complex and the authors´ positions are multiple and diverse. Most of the writers describe these actions as a suicide terrorism motivated by religious beliefs. But also, many other motivations are indicated as having social, cultural, politic and psychological roots. A critical view of the works brings to censure the tendency to consider the violent suicide as the result of muslin religion and culture in its fight against the western democracy and civilization. Some incorrect readings of this kind of suicide as jihad or simply as terrorism or Islamic fundamentalism were criticized because they do not consider their cultural factors. The religious belief was admitted as a relevant factor but not as the chief motivation. The action of the suicide attacker was point out as a gift of life and as a religious experience but it rises a deep ethical dilemma for killing himself and innocent people. Dialogue, solidarity, love and struggle against all forms of barbarism are required to overcome suicide attackers